PENERAPAN SISTEM BOARDING SCHOOL UNTUK MEMBENTUK KARAKTER RELIGIUS SISWA SMP NAMIRA KOTA PROBOLINGGO - Ahmad Fuad Abdul Baqi; Dimas Adji Pangestu; Devy Habibi Muhammad (LPPM STAI Muhammadiyah Probolinggo, 2023)
This research aims to determine the implementation of the Boarding School system for the formation of the religious character of students at Namira Junior High School, Probolinggo. This study uses descriptive qualitative research that produces descriptive data. Sources of data were obtained from the principal, ustadz, ustadzah, assistants, students. Data collection procedures are interviews, observation, and documentation. Data analysis uses data reduction, data presentation, and drawing conclusions. Checking the validity of the data uses observation and triangulation. The research stages conducted were pre-field, field, data analysis stage, and report writing stage. The results of this study indicate that: 1) The implementation of the boarding school system at Namira Middle School, Probolinggo City with the mentoring system runs smoothly. The activities that have been set are carrying out the obligatory prayers in congregation, sunnah prayers, participating in Al-Qur'an teaching activities up to the book every day. 2) The formation of religious character at the Namira Junior High School boarding school in Probolinggo City uses the method of habituation, advice and punishment. 3) The supporting factors in the implementation of the boarding school system are school factors that always fully support, parents factors due to distance of the house and also the desire of the parents for children to take part in the boarding school program so that religious character or good morals are formed, strategic environmental factors to facilitate the implementation of the boarding school system. As for the inhibiting factors, namely students who are lack discipline in carrying out teaching and learning activities.